2020
DOI: 10.5492/wjccm.v9.i4.63
|View full text |Cite
|
Sign up to set email alerts
|

Association between thrombomodulin and high mobility group box 1 in sepsis patients

Abstract: BACKGROUND High mobility group box 1 (HMGB1) has been studied as a molecule associated with severe outcomes in sepsis and thrombomodulin (TM) seems to decrease HMGB1 activity. AIM To investigate the role of the thrombomodulin/high mobility group box 1 (T/H) ratio in patients with sepsis and their association with their clinic, testing the hypothesis that higher ratios are associated with better outcomes. METHODS Twenty patients diagnosed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…High mobility group box 1 (HMGB1) is critical in the pathogenesis of sepsis. [7][8][9] HMGB1 is stored in the nucleus. Bacteria lipopolysaccharide (LPS) can cause HMGB1 acetylation, resulting in the localization of the protein to the cytosol.…”
Section: Introductionmentioning
confidence: 99%
“…High mobility group box 1 (HMGB1) is critical in the pathogenesis of sepsis. [7][8][9] HMGB1 is stored in the nucleus. Bacteria lipopolysaccharide (LPS) can cause HMGB1 acetylation, resulting in the localization of the protein to the cytosol.…”
Section: Introductionmentioning
confidence: 99%
“…15 Research by Rodrigues et al showed that the group of patients with a SOFA score greater than or equal to 12 points had a statistically significantly higher level of sTM than the group with a SOFA score less than 12 points. 25 According to this study, the levels of sTM, IL-6, SOFA score, and APACHE II score in the group that died within 28 days were statistically significantly higher than those in the survival group (p < 0.05). Using ROC analysis, our study showed that the AUC of sTM, IL-6, SOFA score, and APACHE II score in predicting mortality was 0.811, 0.671, 0.816, and 0.705, respectively.…”
mentioning
confidence: 53%
“…sTM concentration can be used to track disseminated intravascular coagulation (DIC) and multiple organ dysfunction syndrome (MODS) as well as sepsis severity and the needs of renal replacement therapy ( 13 , 14 ). Additionally, sTM level strongly associated with the severity of organ dysfunction and therefore is a reliable biomarker in early recognition of sepsis patient, especially one with septic shock ( 15 ).…”
Section: Introductionmentioning
confidence: 99%